Review of the Neural Processes of Working Memory Training: Controlling the Impulse to Throw the Baby Out With the Bathwater - Brooks, Samantha J.; Mackenzie-Phelan, Rhiannon; Tully, Jamie; Schiöth, Helgi B. (Frontiers in Psychiatry, 2020)
Background: Smartphone technology has enabled the creation of many working memory training (WMT) Apps, with those peer-reviewed described in a recent review (Brooks et al., 2020). WMT claims to improve working memory, attention deficits, hyperactivity and fluid intelligence, in line with plasticity brain changes. Critics argue that WMT is unable to achieve ‘far-transfer’ – the attainment of benefits to cognition from one taught context to another dissimilar context – associated with improved quality of life. However, brain changes after a course of WMT in frontoparietal and striatal circuits – that often occur prior to behavioural changes – may be a better indicator of far-transfer efficacy, especially to improve impulse control commonly dysregulated in those with addictive disorders, yet not commonly examined in WMT studies. Method: In contrast to previous reviews, the aim here is to focus on the findings of brain imaging WMT training studies across various imaging modalities that use various paradigms, published via PubMed, Scopus, Medline and Google Scholar. Results: 35 brain imaging studies utilised fMRI, structural imaging (MRI, DTI), functional connectivity, EEG, transcranial direct current stimulation (tDCS), cerebral perfusion and neurogenetic analyses with tasks based on visuospatial and auditory working memory, dual and standard n-back. Discussion: Evidence suggests that repeated WMT reduces brain activation in frontoparietal and striatal networks reflective of increased neural circuitry efficiency via myelination and functional connectivity changes. Neural effects of WMT may persist months after training has ended, lead to non-trained task transfer, be strengthened by auxiliary methods such as tDCS and be related to COMT polymorphisms. WMT could be utilised as an effective, non-invasive intervention for working memory deficits to treat impulse and affective control problems in people with addictive disorders.